Constructing linkage maps in the genomics era with MapDisto 2.0 - Heffelfinger, Christopher; Fragoso, Christopher A.; Lorieux, Mathias (Oxford University Press, 2017)
Motivation: Genotyping by sequencing (GBS) generates datasets that are challenging to handle by current genetic mapping software with graphical interface. Geneticists need new user-friendly computer programs that can analyze GBS data on desktop computers. This requires improvements in computation efficiency, both in terms of speed and use of random-access memory (RAM).